WPŁYW PRAWA RZYMSKIEGO NA KSZTAŁTOWANIE SIĘ WSPÓŁCZESNYCH TEORII SIŁY WYŻSZEJ - Sobczyk, Marek (Zeszyty Prawnicze, 2017)
The Influence of Roman Law on the Creation of the Contemporary Theories of Force Majeure Summary This paper is devoted to the influence of Roman law on the creation of the contemporary theories of force majeure. Its aim is to verify a commonly shared view that Roman law deeply influenced the development of the private law. The Author analyses the works of the nineteenth century legal scholars on the issue of force majeure (L. Goldschmidt, A. Exner, G. Gerth, J. Luchsinger) to examine to what extent their theories and views were based on Roman law. The nineteenth century legislation referred to the doctrine of Roman jurists due to the fact that the notion of force majeure was applied in the same legal relationships as in Roman law (first and foremost the liability of carrier, innkeeper, stablekeeper). Apart from the national terms used to denote force majeure, e. g. German term höhere Gewalt, the legislators applied the original Roman term vis maior which was well-known in legal writing of European countries. The author comes to a conclusion that the above mentioned legal scholars took advantage of the thought of Roman jurists In fact, the scholars searched for the fundamental idea of their doctrines in the sources of Roman law, however, the sources themselves were interpreted in a creative way, to considerable extent abstracted from their content. The Roman law was analyzed taking into account the needs of the nineteenth century legal relations. To sum up: the theories of force majeure consisted of both the thought of Roman jurists and creative concepts of the nineteenth century scholars.